Analysis of Inflation Data Relationships Between DKI Jakarta Province and West Java from 2014 to 2021 Using Vector Autoregressive (VAR) Method (Government and Statistics, 2022)
The provinces of DKI Jakarta and West Java are two regions that are geographically close together and work together, especially in the economic field. Spatially, the inflation rate of these two regions is also interrelated. The study aims to analyze the relationship between inflation rates in DKI Jakarta and West Java Provinces using Vector Autoregressive (VAR) analysis. The data used in this study were monthly inflation data in the provinces of DKI Jakarta and West Java from January 2014 to December 2021. The VAR model obtained in this study was the VAR model with order 2, where the optimal order length was determined from the minimum Akaike Information Criterion (AIC) value. The results of this study indicate that there is a one-way relationship. Namely, the inflation rate in DKI Jakarta Province is influenced by the inflation rate in West Java Province in the previous month. In addition, based on the Impulse Response Function (IRF) analysis, it was found that the inflation rate response in DKI Jakarta Province due to a shock to inflation in West Java Province did not show a response in the first month. Meanwhile, the response to inflation in West Java Province due to shocks to inflation in DKI Jakarta Province showed a positive response in the first and second months. Based on the Variance Decomposition analysis, it was found that the inflation rate in West Java Province contributed little to changes in the inflation rate in DKI Jakarta Province. Meanwhile, the inflation rate in DKI Jakarta Province contributed greatly to changes in inflation rates in West Java Province.
Keywords: inflation; Vector Autoregressive (VAR); DKI Jakarta; West Java; shock